Analysis of the Influence of Organizational Commitment and Budget Participation on Managerial Performance - Widha Hutama, Dusty; Kholmi, Masiyah (International Journal of Management Science and Information Technology, 2025)
This study aims to: (1) analyze the partial influence of organizational commitment on managerial performance. (2) analyze the partial influence of budget participation on managerial performance. Using a quantitative method with 120 respondents who were surveyed and analyzed using the SPSS data processing application. The research results show that: (1) Organizational commitment partially influences managerial performance. (2) Budget participation partially influences managerial performance.